A lean university as an innovative model of university management - V. L. Adzhienko; L. V. Vermennikova; N. S. Davydova; S. K. Kuizheva (Новые технологии, 2021)
Lean production is an innovative paradigm, providing an opportunity for a significant increase in the efficiency of enterprises and organizations of various industries. Currently, the high need for personnel with lean competencies and the expansion of the scope of application of the lean production ideology in the Russian economy have led to the emergence of a new model of management organization in a number of universities – «lean universities». The article analyzes the process and the experience of introducing the lean production principles in a number of Russian universities, identifies the main directions for the emergence of positive effects and the possibilities of forming regional educational systems focused on achieving long-term development goals of a lean individual, the formation of a lean culture in each specific region and country. The object of the research is the organizations of the higher education system in Russia, introducing the principles of lean production in their activities and in the management system. The subject of the research is the role and place of universities in the system of forming lean competencies, creating a flow of development of a lean personality. The article examines the main elements of an innovative model of university management based on the principles of frugality. The formation of an appropriate corporate culture is highlighted as the main condition for the effective functioning of such a model. Its functions consist in forming the worldview of a future specialist, actualize the values of lean production in a personality’s socio-psychological structure, cre- ating a special information-transparent communication environment in the organization that promotes the dissemination of ideas of frugality at the university and beyond. Moreover, the article summarizes the experience of foreign universities that implement the ideas of Lean Production in their activities, and draws analogies with the positive effects that can be observed as a result of the implementation of lean production in the practice of the Russian universities.